Advertising media planning a brand management approach - Kelley, Larry D. 1955-; Dobias, Lisa; Sheehan, Kim Bartel 1958-; Koranda, David E. (Routledge, 2023)
"Advertising Media Planning blends the latest methods for digital communication and an understanding of the global landscape with the best practices of the functional areas of media planning. Taking a unique brand communication approach from an agency perspective, the textbook is organised into four key parts, walking the student through the foundations of brand communication, communication planning, the different media channels available, and the process of preparing, presenting, and evaluating a media plan. This 5th edition has been fully updated to include: - An emphasis throughout on digital and global media planning - New chapters on the role of brand communication, media planning and data analytics, paid media, mobile media, influencer marketing, and B2B media - New mini-case studies and innovation-focused call-out boxes throughout, showcasing media examples from Europe, the USA and Asia - Discussion questions to foster engagement and understanding A highly regarded new edition, this practical and integrated textbook should be core reading for advanced undergraduate and postgraduate students studying Media Planning, Advertising Management, Integrated Marketing Communication and Brand Management. Instructor resources include PowerPoint slides, a test bank and an instructor manual"--